Grillin' wild - Browne, Rick, 1946- (Lyons Press, 2012)
"Grillin' Wild, a cooking show for hunters and fishermen that many consider the best outdoor cooking show on TV, finds creator and host Rick Browne as the Wild Game Chef, sharing recipes from hunting lodges, resorts, preserves, lakes, rivers, oceans, and campground across North America. The Grillin' Wild Cookbook shares the wonderful recipes, cooking tips, and menu suggestions that have made the TV series popular with Browne's audience. Recipes have been gathered from gulf fishing and wild boar hunting in the steamy swamplands of Florida, a trip to Alaska's Chigicoff Island for grilled fresh local shrimp, and many other exotic locations. Rick's new, creative, and easy-to-fix recipes broadly cover the entire range of wild game, game birds, waterfowl, and ocean, lake, and river fish, from Grilled Buffalo Ribeye Steaks with Roquefort Butter, Curried Bear Meatballs, and Grilled Gator Kabobs to Snow Goose with Brandy Sauce, Grilled Halibut with Crab and Shrimp Sauce, and Basil-Ginger Swordfish Steaks"--